2019
DOI: 10.1186/s12964-019-0349-z
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus: mapping and reprogramming the entry

Abstract: Background The flaviviridae family comprises single-stranded RNA viruses that enter cells via clathrin-mediated pH-dependent endocytosis. Although the initial events of the virus entry have been already identified, data regarding intracellular virus trafficking and delivery to the replication site are limited. The purpose of this study was to map the transport route of Zika virus and to identify the fusion site within the endosomal compartment. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…Furthermore, researches of ZIKV endocytosis have broadened our understanding of ZIKV intracellular trafficking in clathrin-mediated endocytosis. ZIKV fusion occurs in late endosomes (Owczarek et al, 2019). It has been increasingly appreciated that many viruses can utilize more than one entryway to infect cells (Kalia et al, 2013;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researches of ZIKV endocytosis have broadened our understanding of ZIKV intracellular trafficking in clathrin-mediated endocytosis. ZIKV fusion occurs in late endosomes (Owczarek et al, 2019). It has been increasingly appreciated that many viruses can utilize more than one entryway to infect cells (Kalia et al, 2013;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…DENV-2 NGC and DENV-3 H87 infection of Vero cells has been previously reported to occur via a clathrin-independent but dynamin-dependent mechanism [ 171 , 172 ]. In general, ZIKV appears to be dependent on CME across divergent strains in diverse cell types [ 173 , 174 ], although a study in neural cells suggested a weak dependence [ 146 ]. Similarly, JEV was reported to infect neuronal cell lineages via a clathrin-independent pathway [ 175 , 176 , 177 ] in contrast to the clathrin-dependent endocytic mechanisms displayed in Vero, C6/36, BHK-21, HeLa and PK15 cells [ 178 , 179 , 180 , 181 , 182 ].…”
Section: Endocytic Pathways Mediating Mosquito-borne Flavivirus Inmentioning
confidence: 99%
“…The P2 peptide is a water-soluble molecule but could not enhance APP expression when treating cells directly (data not shown). It is known that the interactions between BACE1 and APP protein happen in both biosynthetic and endocytic compartments inside cells (60,61), and ZIKV E protein was predicted to bind targets in the endosomal compartments (62,63). Therefore, we transfected P2 peptide into cells to ensure the peptide could meet APP in endocytic compartments physically.…”
Section: Zikv Enhances App Protein Expressionmentioning
confidence: 99%